Exploring the experiences of after-school programme practitioners in the Western Cape in supporting their rural/peri-urban community during the COVID-19 pandemic - Dees, Sandy (Stellenbosch : Stellenbosch University, 2024)
Thesis (MEdPsych)--Stellenbosch University, 2024.